APLAR recommendations on the practice of telemedicine in rheumatology. (19th January 2022) - Ahmed, Sakir; Grainger, Rebecca; Santosa, Anindita; Adnan, Asal; Alnaqbi, Khalid A.; Chen, Yi‐Hsing; Kavadichanda, Chengappa; Kaw, Nang San Kyauk; Kelly, Amy; Khan, Saira Elaine Anwer; Masri, Basel; Nakarmi, Shweta; et al.
Abstract: Introduction: The COVID‐19 pandemic led to rapid and widespread adoption of telemedicine in rheumatology care. The Asia Pacific League of Associations for Rheumatology (APLAR) working group was tasked with developing evidence‐based recommendations for rheumatology practice to guide maintenance of the highest possible standards of clinical care and to enable broad patient reach. Materials and methods: A systematic review of English‐language articles related to telehealth in rheumatology was conducted on MEDLINE/PubMed, Web Of Science and Scopus. The strength of the evidence was graded using the Grading of Recommendations, Assessment, Development and Evaluations (GRADE) approach as well as the Oxford Levels of Evidence. The recommendations were developed using a modified Delphi technique to establish consensus. Results: Three overarching principles and 13 recommendations were developed based on identified literature and consensus agreement. The overarching principles address telemedicine frameworks, decision‐making, and modality. Recommendations 1‐4 address patient suitability, triage, and when telemedicine should be offered to patients. Recommendations 5‐10 cover the procedure, including the means, data safety, fail‐safe mechanisms, and treat‐to‐target approach. Recommendations 11‐13 focus on training and education related to telerheumatology. Conclusion: These recommendations provide guidance for the approach and use of telemedicine in rheumatology care to guide highest possible standards of clinical care and to enable equitable patient reach. However, since evidence in telemedicine care in rheumatology is limited and emerging, most recommendations will need further consideration when more data are available.